Factors influencing parental decision to consult for children with upper respiratory tract infection - Ng, Chirk Jenn; Chia, Y.C.; Teng, C.L.; Nik-Sherina, H. (Wiley, 2008)
Aim: This study aimed to determine which factors could influence (i) parents' decision to seek medical consultatin and (ii) their preference for either public or private medical service in children with upper respiratory tract infection. Methods: This cross-sectional study was conducted at the Gombak district, which is an urban area in Malaysia. We randomly selected parents of kindergarten children aged 4-5 years to participate in this questionnaire survey. The main outcome measures were predictors of early medical consultation and type of service utilisation (public versus private). Results: We achieved a response rate of 84.5 (n = 1033/1223). 64.1 sought early medical consultation and 70.9 preferred to consult a private doctor. Early consultation was predicated by the parent gender being male (OR 1.50; 95 CI 1.09, 2.05), non-Chinese (OR 1.75; 95 CI 1.10, 2.79), and those who preferred child specialists (OR 2.02; 95 CI 1.27, 3.23). Lower income group (OR 4.28; 95 CI 2.30, 7.95) and not having a regular doctor (OR 4.99; 95 CI 3.19, 7.80) were predictors of using the public health services. Conclusions: Parent's gender, ethnicity and income influenced their decision to seek early medical consultation for their children's respiratory illness while income and having a regular doctor could predict their choice of healthcare services.